If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + (-3) = (-18) x + -3 = (-18) Reorder the terms: -3 + x = (-18) -3 + x = -18 Solving -3 + x = -18 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + x = -18 + 3 Combine like terms: -3 + 3 = 0 0 + x = -18 + 3 x = -18 + 3 Combine like terms: -18 + 3 = -15 x = -15 Simplifying x = -15
| -72+12x+-8x^2+x^3=0 | | x-(-36.5)=(-2.563) | | 2sin^2(x)+sin(x)=1 | | -72+12x+-8x^2+x^3=0*2 | | x+x-26=560 | | a-18=(-32) | | x^2+16-36=0 | | 3sin^2x=2sinx+5 | | -72+12x+-8x^2+x^3=0*3 | | -72+12x+-8x^2+x^3=0*4 | | x-4.7=-8.3 | | 7x=221 | | n^2-16n+50=2 | | 3y+5y+10=22 | | (x)=4.4x+3.6 | | x(x-6)(x-2)-72=0 | | 10x+3y-50=0 | | x^3-12x^2+38x-14=0 | | X+3=8-2xk | | 3+15a+18b= | | X+3=8-2x | | x-36=x^2-11x | | x-36=x^2-11 | | -4a+4+5a=6-27 | | 5(2x+3)-8x=7 | | 15r^2+10rs+6rs+4s^2= | | 3.5=3(4+.5) | | 14.1-7.1(x+0.9)=12-5(x+3) | | x^2-x-4=20 | | k^2-6k-143=0 | | X^2-(x-2)(x-2)=20 | | 69=x+(y-7) |